Contribution of the Telecommunications Industry to Sustainable Development Goals within the Framework of SASB General Issue Categories: The Case of a Telecommunications Company - Şimşek, Kezban (Journal of the Human and Social Sciences Researchers, 2024)
Sustainable development is an important issue that shapes the future of our planet by addressing economic, social and environmental factors. The United Nations (UN) has set 17 Sustainable Development Goals (SDGs) to ensure sustainable development, the success of which depends on global cooperation and joint efforts. The SDGs set out the environmental, social and economic sustainability issues to be achieved by 2030. Private sector efforts have an important role in achieving these goals. As a result of social responsibility and stakeholder demands, companies share their sustainability activities and the SDGs to which these activities contribute through reports. Telecommunications companies also have the potential to play a key role in achieving many SDGs through the innovative, accessible and inclusive digital infrastructure systems they provide. This study’s goal is to reveal the impact of the telecommunications industry on the SDGs through the Sustainability Accounting Standards Board's (SASB) General Issue Categories (GIC). In this context, a methodological framework developed by SASB to identify important sustainability issues across sectors and industries matched SDGs with 26 general sustainability issues. In this framework, SDG impact indices were calculated for the technology and communication sector, which includes the telecommunications industry, and for a telecommunications company operating in Turkey, and SDG impact at the sector, industry and company level was tried to be revealed. According to the calculations, it was concluded that the goal known as SDG 9, which was established to establish strong infrastructures, support sustainable industrialization and strengthen and expand innovation, has an impact score of 37.50% for the telecommunication services industry, 31.25% for the technology&communication sector and 31.25% for the sample telecommunication company. SDG 9 has the highest impact score in telecommunications compared to other SDGs.
Keywords: Kalkınma Ekonomisi - Mikro; İşletme; Sustainable Development Goals; Sustainability Reporting; Telecommunications Industry; Materiality analysis; SASB General Issue Category; Developmental Economy - Micro; Sürdürülebilir Kalkınma Hedefleri; Sürdürülebilirlik Raporlaması; Telekomünikasyon Endüstrisi; Önemlilik Analizi; SASB Genel Konu Kategorisi; Business Administration